Skrining Fitokimia dan Evaluasi Antibakteri Ekstrak NADES (Natural Deep Eutectic Solvents) Daun Iler (Coleus atropurpureus L. Benth) terhadap Bakteri Penyebab Folikulitis - Ulfa, Evi Umayah; Pratama P., M. Reynaldi Archan; Dianasari, Dewi (Faculty of Pharmacy, University of Jember, 2024)
The iler plant (Coleus atropurpureus) can be used as an efficacious medicinal plant. The chemical contents of the iler plant include essential oils, alkaloid, polyphenols, tannins and flavonoids. This content can be used as an antibacterial. This study aims to determine the antibacterial activity of iler leaves (Coleus atropurpureus) against bacterial folliculitis (Staphylococcusaureus). The NADES combination used is choline chloride:sorbitol with a ratio of 1:1, 2:1, and 3:1. The extraction method uses the UAE method and the antibacterial activity test uses the well diffusion method. The positive control used was Ciprofloxacin. The diameter of the inhibition zone for S. aureus bacteria is in a ratio of 1:1 (4,53 mm), 2:1 (6,29 mm), and 3:1 (8,12). The results of the phytochemical screening test obtained showed that the NADES extract of Iler leaves was positive for containing alkaloids, flavonoids, polyphenols and tannins.